The Influence of The Use of Digital Comics Vs E-Books and Learning Motivation on The Learning Outcomes of History of Class XI Social Studies Students of SMA Negeri 2 and 4 Probolinggo - Mis Endang Sutin; Rufi`i; Ibut Priono Lesono (IAIN Madura, 2022)
The quality of learning is largely determined by teachers. They are required to be skilled in bringing and guiding their students so that they can learn optimally. The objectives of this study are: (1) To find out how much influence the use of digital comics vs. e-books has on the learning outcomes of class XI social studies students at SMA Negeri 2 and SMA Negeri 4 Probolinggo. (2) To find out how much influence of the use of digital comics vs e-books and high and low student motivation is on the learning outcomes of class XI social studies students at SMA Negeri 2 and SMA Negeri 4 Probolinggo. (3) To find out whether or not there is interaction in the use of digital comic media vs e-books and learning motivation towards the learning outcomes of class XI social studies students at SMA Negeri 2 and SMA Negeri 4 Probolinggo. The data collection technique is learning outcomes using tests and for motivation using questionnaires, and data analysis using 2-pathway variance analysis (Anava). The conclusions of this study are: 1) There is an influence on the use of digital comics vs e-books on learning outcomes 2) There is an influence on the use of digital comics vs e-books and high and low student motivation on learning outcomes. 3) There is an interaction in the use of digital comic media vs e-books and learning motivation towards learning outcomes. In learning activities in the 21st century era, teachers are advised to provide and use digital media such as digital comics, so that students are interested in learning. Thus, students can be active and understand the material taught by the teacher and can improve their learning achievement.